Effect of electroencephalogram-guided anesthesia on postoperative delirium in older adults after surgery: a systematic review and meta-analysis - Da, Xiang; Li, Xia; Dong, Anmin; Chen, Li; Ma, Youjia; Li, Xue (Frontiers in Neurology, 2025)
BackgroundPostoperative delirium is a frequent and severe complication among elderly surgical patients. Electroencephalogram (EEG)-guided anesthesia, which optimizes sedation depth, holds promise for preventing postoperative delirium; however, current research findings remain inconsistent. This meta-analysis incorporates the most recent trials to evaluate the effectiveness of EEG-guided anesthesia in reducing postoperative delirium incidence in older adults.MethodsWe conducted a comprehensive literature search of PubMed, the Cochrane Central Register of Controlled Trials, and Embase from their inception to February 1, 2025, to identify eligible studies. This systematic review and meta-analysis aimed to evaluate the effectiveness of electroencephalogram-guided anesthesia in preventing postoperative delirium among elderly surgical patients. Pooled effect estimates for all outcomes were calculated using a random-effects model. The quality and certainty of the evidence were assessed using the GRADE methodology. The primary outcome was the occurrence of postoperative delirium.ResultsOf the 3,151 studies screened, 12 were deemed eligible for inclusion, encompassing a total of 7,441 patients, of whom 3,707 received EEG-guided anesthesia. Compared with standard care, EEG-guided anesthesia demonstrated a beneficial effect in reducing postoperative delirium among elderly patients (RR = 0.76, 95% CI: 0.61–0.96), as well as the incidence of postoperative infections (RR = 0.74, 95% CI: 0.58–0.95). Subgroup analyses revealed no significant interaction based on type of surgery (p = 0.18).ConclusionEEG-guided anesthesia is associated with a reduced incidence of postoperative delirium in elderly surgical patients.